Analysis of Cancer Knowledge, Attitudes, and Practices in Adolescents and Young Adults in Two Texas Rural Communities. (20th April 2022) - Moya, Eva M; Chávez-Baray, Silvia; Garcia, Araceli; McCreary, Robert
The Youth and Young Adults Cancer Knowledge Attitudes and Practices (C-KAP) exploratory study in 2 rural underserved areas in a border community. C-KAP is an interdisciplinary research pilot project led by university scholars in psychology and social work in partnership with community partners. The exploratory cross-sectional mix-method study recruited 141 (n = 141) youth and young adults (ages 18-39). This study was informed on empirical research and a bilingual online questionnaire was field-tested, and data was collected via QuestionPro Software. Quantitative analysis was conducted using SPSS version 27. Descriptive statistics and frequency analysis were used for demographics and basic statistics. Chi square tests and Fisher's exact tests between variables were ran to find statistically significant associations. For the qualitative data, independent coders conducted recurrent content analysis to identify themes. Salient themes include knowledge about cancer types; access to health care; prevention; and the perceived impact of COVID-19 pandemic. Findings highlight a lack of knowledge and orientation on cancer in youth and young adults suggesting the need for community tailored education and screening interventions. Other findings reflect gender differences in knowledge and practices, which indicates that a gender-specific lens is needed when delivering education.